Proceedings of the Third International Conference on Sustainable Innovation 2019 – Health Science and Nursing (IcoSIHSN 2019) 2019
DOI: 10.2991/icosihsn-19.2019.9
|View full text |Cite
|
Sign up to set email alerts
|

Fraction From Rice Bran Oil Using Ultrasonic Methods and Analysis Of Antioxidant Effectiveness

Abstract: Rice (Oryza sativa) is one of the main cereals in the world, especially in Asian countries. Rice bran, one of the byproducts of rice dehulling, has gained a lot of popularity as a functional foodstuff in recent years. The purpose of this study was to extract Ferulic Acid from the phenolic fraction of rice bran oil using the ultrasonic method, followed by antioxidant effectiveness analyses. Oil was extracted from rice bran using the ultrasonic method in an ethanol solvent. The result was analyzed for phenol yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The present study showed that rice bran yielded a higher amount of FA than bamboo shoot and wheat bran. Recent studies also unveiled the fact that rice bran is a rich source of antioxidant molecules such as γ-oryzanol and ferulic acid (Arumsari et al, 2019;Tam et al, 2021). The extraction of Ferulic acid has been found much attention nowadays because it exhibits a wide variety of biological activities, including antimicrobial, antiinflammatory, anti-thrombosis, anticancer, and antioxidant activities.…”
Section: Chromatographic Studiesmentioning
confidence: 99%
“…The present study showed that rice bran yielded a higher amount of FA than bamboo shoot and wheat bran. Recent studies also unveiled the fact that rice bran is a rich source of antioxidant molecules such as γ-oryzanol and ferulic acid (Arumsari et al, 2019;Tam et al, 2021). The extraction of Ferulic acid has been found much attention nowadays because it exhibits a wide variety of biological activities, including antimicrobial, antiinflammatory, anti-thrombosis, anticancer, and antioxidant activities.…”
Section: Chromatographic Studiesmentioning
confidence: 99%
“…According to Ref. [ 2 ], rice bran oil is highly nutritious and contains unsaturated fatty acid and antioxidants like oryzanol, to-copherol, tocotrienol, phytosterol, polyphenol, and squalene. Ferulic Acid (FA) is a part of phenol fraction with the highest yield of 24 % at 80 % ethanol concentration and Ultra-sonication extraction method.…”
Section: Introductionmentioning
confidence: 99%
“…Rice to be consumed must first be separated from the skin, which can produce solid waste. Solid waste from rice separation is referred to as rice bran [1] [2]. Generally, the rice bran produced from the rice milling process is as much as 8-12%.…”
Section: Introductionmentioning
confidence: 99%